2002
DOI: 10.1073/pnas.182420899
|View full text |Cite
|
Sign up to set email alerts
|

PPARα is necessary for the lipopenic action of hyperleptinemia on white adipose and liver tissue

Abstract: Adenovirus-induced hyperleptinemia causes rapid disappearance of body fat in normal rats, presumably by up-regulating fatty acid oxidation within white adipocytes. To determine the role of peroxisomal proliferation-activated receptor (PPAR)␣ expression, which was increased during the rapid loss of fat, we infused adenovirus-leptin into PPAR␣ ؊/؊ and PPAR␣ ؉/؉ mice. Despite similar degrees of hyperleptinemia and reduction in food intake, epididymal fat pad weight declined 55% in wild-type but only 6% in PPAR␣ ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 22 publications
7
111
0
1
Order By: Relevance
“…Besides the well-established systemic effect of PPAR␣ agonists on energy expenditure and fat oxidation, it has recently been suggested that activation of the nuclear receptor in WAT could prevent adipocyte hypertrophy (36). In line with this concept, PPAR␣ is essential for the lipopenic effect of hyperleptinemia on WAT (37). Furthermore, PPAR␣ mediates the action of a ␤ 3 -adrenergic receptor agonist on WAT gene expression and remodeling (21).…”
Section: Discussionmentioning
confidence: 96%
“…Besides the well-established systemic effect of PPAR␣ agonists on energy expenditure and fat oxidation, it has recently been suggested that activation of the nuclear receptor in WAT could prevent adipocyte hypertrophy (36). In line with this concept, PPAR␣ is essential for the lipopenic effect of hyperleptinemia on WAT (37). Furthermore, PPAR␣ mediates the action of a ␤ 3 -adrenergic receptor agonist on WAT gene expression and remodeling (21).…”
Section: Discussionmentioning
confidence: 96%
“…This nuclear receptor has critical roles in energy metabolism, hepatic steatosis, inflammation, cardiac pathophysiology, cell cycle regulation, and oncogenesis (31,32). In hepatic cells, the modulatory action of bile acids on PPAR␣-mediated transactivation has been shown to affect the expression of genes, including those involved in lipid homeostasis (24,33).…”
Section: Discussionmentioning
confidence: 99%
“…Because PGC-1␣ is involved in mitochondrial biogenesis (21-23), its increase may have played a role in the abundance of mitochondria in postadipocytes. Indeed, when PGC-1␣ is not increased, as in fat cells of adenovirus-leptin-treated PPAR␣-null mice, the hyperleptinemia fails to induce adipocyte fat loss (12). Because forced expression of PGC-1␣ in human fat cells enhances their oxidation of fatty acids (24), it is quite likely that its increase was responsible for the loss of fat through ''internal combustion.''…”
Section: Discussionmentioning
confidence: 99%